OPTIMALISASI DIGITAL ECONOMY DAN BRAND IDENTITY DALAM IMPLEMETASI DIGITALISASI UMKM PETANI KOPI GUNA PENINGKATAN PEMBERDAYAAN MASYARAKAT KELOMPOK TANI JAWA BARAT - Bambang Suprayogi; Abdur Razak; Muhammad Ridwansyah (POLITEKNIK LP3I JAKARTA, 2025)
Product packaging and Brand of UMKM Coffee Farmers in Cilengkrang District, Bandung Regency, West Java Province greatly influence the way customers view products, and with the implementation of the digital economy, this can help business income and with the running of this business well, it can continue to increase the income of UMKM Coffee Farmers in Cilengkrang District, Bandung Regency, West Java Province. The role of the Digital Economy in terms of product packaging and Brand in UMKM Coffee Farmers in Cilengkrang District, Bandung Regency, West Java Province facilitates the sales process, facilitates payment transactions and helps product marketing. Specifically, UMKM in this study are UMKM Coffee Farmers in Cilengkrang District, Bandung Regency, West Java Province who are not yet productive, economically independent and have not been effective in using technology in the management and Marketing of UMKM Coffee Farmers in Cilengkrang District, Bandung Regency, West Java Province which are still limited.